Use logarithmic differentiation to find dy/dx y=x sqrt{x^2+48}

Question
Differential equations
Use logarithmic differentiation to find
dy/dx y=x sqrt{x^2+48}ZSK

2021-01-01
$$\displaystyle{y}={x}\sqrt{{{x}^{{2}}+{48}}}$$
$$\displaystyle{y}={x}\cdot{\left\lbrace{x}^{{2}}+{48}\right\rbrace}^{{\frac{{1}}{{2}}}}$$
Taking logs of both sides.
$$\displaystyle{\ln{{\left({y}\right)}}}={\ln{{\left({x}\right)}}}+{\left(\frac{{1}}{{2}}\right)}{\ln{{\left({x}^{{2}}+{48}\right)}}}$$
differentiating both sides wrt x,
$$\displaystyle{\left(\frac{{1}}{{y}}\right)}{y}'=\frac{{1}}{{x}}+{\left(\frac{{1}}{{2}}\right)}\frac{{{2}{x}}}{{{x}^{{2}}+{48}}}$$
$$\displaystyle{y}'=\frac{{y}}{{x}}+\frac{{{y}{x}}}{{{x}^{{2}}+{48}}}$$
$$\displaystyle{y}'=\sqrt{{{x}^{{2}}+{48}}}+{\left({x}^{{2}}\right)}\frac{\sqrt{{{x}^{{2}}+{48}}}}{{{x}^{{2}}+{48}}}$$
$$\displaystyle{y}'=\frac{{{x}^{{2}}+{48}}}{\sqrt{{{x}^{{2}}+{48}}}}+\frac{{{x}^{{2}}}}{\sqrt{{{x}^{{2}}+{48}}}}$$
$$\displaystyle\frac{{\left.{d}{y}\right.}}{{\left.{d}{x}\right.}}=\frac{{{2}{x}^{{2}}+{48}}}{\sqrt{{{x}^{{2}}+{48}}}}$$
$$\displaystyle\frac{{\left.{d}{y}\right.}}{{\left.{d}{x}\right.}}={2}\frac{{{x}^{{2}}+{24}}}{\sqrt{{{x}^{{2}}+{48}}}}$$

Relevant Questions

Solve the equation:
$$\displaystyle{\left({x}+{1}\right)}{\frac{{{\left.{d}{y}\right.}}}{{{\left.{d}{x}\right.}}}}={x}{\left({y}^{{2}}+{1}\right)}$$
Solve the equation:
$$\displaystyle{\left({a}-{x}\right)}{\left.{d}{y}\right.}+{\left({a}+{y}\right)}{\left.{d}{x}\right.}={0}$$
The graph of y = f(x) contains the point (0,2), $$\displaystyle{\frac{{{\left.{d}{y}\right.}}}{{{\left.{d}{x}\right.}}}}={\frac{{-{x}}}{{{y}{e}^{{{x}^{{2}}}}}}}$$, and f(x) is greater than 0 for all x, then f(x)=
A) $$\displaystyle{3}+{e}^{{-{x}^{{2}}}}$$
B) $$\displaystyle\sqrt{{{3}}}+{e}^{{-{x}}}$$
C) $$\displaystyle{1}+{e}^{{-{x}}}$$
D) $$\displaystyle\sqrt{{{3}+{e}^{{-{x}^{{2}}}}}}$$
E) $$\displaystyle\sqrt{{{3}+{e}^{{{x}^{{2}}}}}}$$
Use the Differentiation Formulas and Rules of Derivatives to find the derivatives of the following functions.
$$\displaystyle{g{{\left({y}\right)}}}={\left({y}-{4}\right)}{\left({2}{y}+{y}^{{{2}}}\right)}$$
g'(y)=
Use the Differentiation Formulas and Rules of Derivatives to find the derivatives of the following functions.
$$\displaystyle{h}{\left({y}\right)}={2}{y}^{{-{4}}}-{7}{y}^{{-{3}}}+{4}{y}^{{-{2}}}+{\frac{{{11}}}{{{y}}}}$$
$$\displaystyle{h}'{\left({y}\right)}=$$
Make and solve the given equation $$x\ dx\ +\ y\ dy=a^{2}\frac{x\ dy\ -\ y\ dx}{x^{2}\ +\ y^{2}}$$
find general solution in semi homogenous method of $$\displaystyle\frac{{\left.{d}{y}\right.}}{{\left.{d}{x}\right.}}={x}-{y}+\frac{{1}}{{x}}+{y}-{1}$$
Find the differential dy for the given values of x and dx. $$y=\frac{e^x}{10},x=0,dx=0.1$$
$$\displaystyle{\frac{{{d}}}{{{\left.{d}{x}\right.}}}}{\int_{{{0}}}^{{{x}}}}{e}^{{\sqrt{{{t}}}}}{\left.{d}{t}\right.}$$